Development of Scratch-Based Educational Games Media to Enhance Natural Sciences and Social Sciences (IPAS) Learning Outcomes in Elementary School - Amalia, Maya Nur; Sukasih, Sri (Jurnal Paedagogy, 2025)
This study aims to develop scratch-based educational game media to enhance Natural Sciences and Social Sciences (IPAS) Learning Outcomes in Elementary School. The research uses a Research and Development method with the ADDIE model, which has five stages, namely Analyze, Design, Development, Implement, and Evaluate. The subject of this study were fourth-grade elementary school students. Data were collected through questionnaires containing questions and interviews for teachers and students, and observastion of learning. The results of this study showed that scratch-based educational game media can significantly increase student learning outcomes, especially in elementary school IPAS learning. This is evidenced by statistical analysis through a paired sample t-test shows a significant result of 0.000, because the significant result is below 0.05. The development of scratch-based education game media is considered to provide a different learning experience because students can explore learning directly. With the increased participation of students, the learning outcomes obtained will also increase. The practicality of using scratch-based educational game media obtained a score of 86.5%, which indicates that it is very feasible and practical to use.